Predictors of self-management in patients with chronic low back pain: a longitudinal cohort study protocol - Banerjee, Anirban; Hendrick, Paul; Blake, Holly (AA Publications, 2016)
Studies on self-management (SM) support programmes in chronic low back pain (CLBP) have failed to show clinically meaningful treatment benefit, which potentially highlights lack of research on predictors of effective SM. The purpose of this multi-centre non-experimental longitudinal cohort study is to identify the predictors of SM and its change over time in community ambulant adults (18-65 years) who are attending or have recently attended outpatient physiotherapy for their CLBP (approx. n=400). Self-reported validated measures for SM, pain intensity, disability, physical activity level, kinesiophobia, catastrophising, depression and global impression of change will be recorded at baseline and six-months. Descriptive statistics, correlation and multiple regression will be employed for the primary data analyses. This study protocol has ethical approval and is registered in ClinicalTrials.gov (ID: NCT02636777). Study results will inform patient selection for SM support in CLBP, and the development of tailored and targeted SM support programmes for this patient group.